The effectiveness of gamified learning environments in promoting grammar mastery in Jordanian secondary school EFL learners - Abdulbaki, Shatha; Khasawneh, Mohamad A. S.; Tashtoush, Mohammad A. (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the effectiveness of gamified learning environments in improving grammar mastery and engagement among Jordanian secondary school EFL learners in Saudi Arabia. The research aims to explore the impact of gamification on learners’ cognitive, emotional, and behavioral engagement while addressing the challenges faced in grammar instruction within this educational context. A quantitative experimental research design was employed, involving 120 students divided into an experimental group (exposed to a gamified grammar intervention) and a control group (taught using traditional methods). Data were collected through pre-tests, post-tests, and engagement questionnaires. Statistical analyses, including ANCOVA and effect size evaluation, were conducted to determine the impact of gamification on grammar proficiency and student engagement. The results indicate a significant improvement in grammar mastery among students in the gamified learning environment, with a 41.91% increase in proficiency compared to 13.41% in the control group. The experimental group also demonstrated higher scores in behavioral, emotional, and cognitive engagement, confirming that gamification enhances both learning outcomes and student motivation. Effect size analysis revealed a large impact of gamification on grammar achievement and engagement levels. This study provides empirical evidence supporting gamified learning as an effective strategy for enhancing grammar acquisition in EFL contexts. The findings highlight the role of gamification in fostering engagement and improving learner performance, suggesting that it can serve as a transformative approach in language education. The study offers valuable insights for educators, curriculum developers, and policymakers, emphasizing the need to integrate gamification into EFL instruction. By incorporating game-based elements, teachers can create a more engaging and effective learning environment, potentially improving long-term grammar retention and student motivation. Additionally, cultural considerations should be taken into account when implementing gamified learning to ensure its effectiveness across diverse educational settings.